Microglia Phenotype and Intracerebral Hemorrhage: A Balance of Yin and Yang - Bi, Rentang; Fang, Zhi; You, Mingfeng; He, Quanwei; Hu, Bo (Frontiers in Cellular Neuroscience, 2021)
Intracerebral hemorrhage (ICH) features extremely high rates of morbidity and mortality, with no specific and effective therapy. And local inflammation caused by the over-activated immune cells seriously damages the recovery of neurological function after ICH. Fortunately, immune intervention to microglia has provided new methods and ideas for ICH treatment. Microglia, as the resident immune cells in brain, play vital roles in both tissue damage and repair processes after ICH. The perihematomal activated microglia not only arouse acute inflammatory responses, oxidative stress, excitotoxicity and cytotoxicity to cause neuron death, but also show another phenotype that inhibit inflammation, clear hematoma and promote tissue regeneration. The proportion of microglia phenotypes determines the progression of brain tissue damage or repair after ICH. Therefore, microglia may be a promising and imperative therapeutic target for ICH. In this review, we discuss the dual functions of microglia in brain after ICH from immunological perspective, elaborate on the activation mechanism of perihematomal microglia, and summarize related therapeutic drugs researches.